Dried rose petals: From the kitchen to the boudoir - Malakar, Moumita (Indian Horticulture, 2022)
Rose is a universally acknowledged and admired flower. The extortionate price, high perishability, unavailability round the year and ephemeral nature of fresh cut roses eventually abashing passionate rose lovers. So to keep this favourite flower around all year long, drying is the most exercised and exemplary approach. Not only dehydrated rose, anyone can also experience the worthwhile consequences of desiccated rose petals. Dried rose petals in particular can be transformed into many wonderful things. On top of all that, the process of drying them is actually quite simple. They provide an intoxicating fragrance to potpourri and satin sachets, add colour to indoor decorations and create romantic confetti for weddings. Although the spectacular sight and heavenly scent of the flowers do not last long and soon give way to the red coloured rose hips but it is hard not to love a rose. So to preserve its show-stopping aroma and protean utilities, dried rose petals are the pre-eminent recourse.